The Role of Strategic Planning in Enhancing Cloud-Based Business Intelligence to Achieve Organizational Goals in Jordanian Commercial Banks - Khawaldeh, Khaldoon; Awamleh, Fawwaz Tawfiq (International Review of Management and Marketing, 2026)
The specific area studied in this research is the significance of strategic planning and its implications on improving cloud business intelligence (BI) among thirteen commercial banks located in the Kingdom of Jordan. To investigate the impact of cloud business intelligence, the authors distributed e-questionnaires to a sample size of 328 administrative staff members from different banks, to assess how strategic planning affects the deployment and efficiency of cloud-based business intelligence systems. Results showed that there existed a very strong relationship between the application of strategic planning and the efficiency of cloud business intelligence system deployment at the banks. Banks with proper and well-structured strategic plans performed better and more effectively with their decision-making and management processes. Additionally, the study showed that the application of strategic planning aids banks significantly in improving the link between the application of technology and the organization’s goals and strategies. The alignment of process could give banks greater analytical capabilities and to derive competitive advantage. This study serves as an addition to the knowledge of how the application of better management strategies further aids banks in the application of technology. The relevance of business intelligence on the cloud must therefore well fit with the management strategies of banks as the banks need to be capable of thriving on a sustained cloud environment. This study serves as an addition to the knowledge of how the application of better management strategies further aids banks in the application of technology. Additionally, the application of business intelligence on cloud technology needs proper coordination with management strategies at banks if banks are looking forward to performing effectively on a sustained cloud platform.